Singapore Eurasians Memories, Hopes and Dreams - Blake, Myrna L.; Ebert-Oehlers, Ann; Pereira, Alexius A. (World Scientific series on Singapore's 50 years of nation-building., 2017)
"Singapore Eurasians: Memories, Hopes and Dreams offers insight into the Singapore Eurasian community, one of Singapore's minority communities. Though small, the Eurasian community has undoubtedly played a big part in Singapore's nation-building. This book is the definitive record of Eurasian history and heritage in Singapore, and serves to educate the younger generation of Eurasians about their roots, the community's achievements and its collective hopes and dreams for the future, as well as provide a useful resource for others to learn more about the Eurasian community. In addition, Singapore Eurasians: Memories, Hopes and Dreams also covers the growth and developments of the Eurasian community within the last 25 years, and how the Eurasian Association (EA), as a Self-Help Group since 1994, has been helping the less fortunate through its programmes, as well as being the main force in driving the preservation and sharing of the Eurasian culture for its future generations. In preserving the history, heritage, hopes and dreams of the Singapore Eurasian community, this book is an effort in contributing to the country's continued multiracial harmony and appreciation of the many elements that make up Singapore's story".